Single-nucleotide resolution detection of Topo IV cleavage activity in the Escherichia coli genome with Topo-Seq - Sutormin, Dmitry; Galivondzhyan, Alina; Gafurov, Azamat; Severinov, Konstantin (Frontiers in Microbiology, 2023)
Topoisomerase IV (Topo IV) is the main decatenation enzyme in E. coli; it removes catenation links that are formed during DNA replication. Topo IV binding and cleavage sites were previously identified in the E. coli genome with ChIP-Seq and NorfIP. Here, we used a more sensitive, single nucleotide resolution Topo-Seq procedure to identify Topo IV cleavage sites (TCSs) genome-wide. We detected thousands of TCSs scattered in the bacterial genome. The determined cleavage motif of Topo IV contained previously known cleavage determinants (-4G/+8C, -2A/+6T, -1T/+5A) and additional, not observed previously, positions -7C/+11G and -6C/+10G. TCSs were depleted in the Ter macrodomain except for two exceptionally strong non-canonical cleavage sites located in 33 and 38 bp from the XerC-box of the dif-site. Topo IV cleavage activity was increased in Left and Right macrodomains flanking the Ter macrodomain and was especially high in the 50-60 kb region containing the oriC origin of replication. Topo IV enrichment was also increased downstream of highly active transcription units, indicating that the enzyme is involved in relaxation of transcription-induced positive supercoiling.